Unilateral open lip schizencephaly: a case report - Prabahita Baruah; Pradipta Ray Choudhury; Prashant Sarda (Wolters Kluwer Medknow Publications, 2015)
Schizencephaly is a rare malformation of the central nervous system defined as a gray matter-lined cleft filled with cerebrospinal fluid that extends from the pial surface to the ventricle. We present a case of a 16 year old male patient with intractable epilepsy where Computed Tomography scan revealed a grey matter lined cleft on the right cortical surface communicating with ipsilateral lateral ventricle.